The socio-political significance of changes to the vocational education system in Germany - Kupfer, Antonia [Verfasser] (My University, 2010)
"This paper explores the effects on social inequality in Germany of ongoing changes to the employment system and, thus, vocational education. Results based on an examination of the literature indicate that students from increasingly middle-class backgrounds with higher levels of general, rather than vocational, educational attainment are winning the competition for ever-fewer apprenticeships. Progress for women in education is accompanied by relative declines in men’s performance on high school exit examinations and does not translate into success in the employment system. Employers are abandoning the corporate-state organization of vocational education. The paper concludes that school degrees are increasingly important for later career opportunities. As a result, the educational system is increasingly stratified, contributing to social inequality in Germany." (Autorenreferat, BIBB-Doku)
Keywords: T 4.5 Soziologie; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Bildungssoziologie; Soziale Ungleichheit; Bildungschancengleichheit; Soziale Schichtung; Segmentation; Geschlechterdifferenz; Geschlechtersegregation; Bildungsniveau; Gleichwertigkeit; Allgemeinbildung; Berufsbildung